Upaya Peningkatan Hasil Belajar Ekonomi Dengan Media Word Square Pada Siswa Kelas XI IPS - Devi Yulianti (Jurnal Studi Sosial / Journal of Social Studies, 2017)
The objectives of the study were to describe the learning outcomes of the students in the experimental group with word square media, (2) to describe the students 'learning result of the control group and the conventional learning (3) to know the difference between the students' learning achievement with word square media and the conventional learning. Data were analyzed using t-test. The result of the study found that (1) the learning result of IPS students with word square learning media included in the high category, (2) the students 'economic learning result with conventional learning included in medium category, (3) there is significant difference in the students' students with word square media and groups of students with conventional learning). It can be concluded that the use of word square learning media influence to improve students' economic learning outcomes. Penelitian bertujuan (1) mendeskripsikan hasil belajar Ekonomi siswa kelompok eksperimen dengan media word square, (2) mendeskripsikan hasil belajar Ekonomi siswa kelompok kontrol dengan pembelajaran konvensional (3) mengetahui perbedaan antara hasil belajar Ekonomi siswa dengan media pembelajaran word square dan dengan pembelajaran konvensional. Data dianalisis dengan menggunakan uji-t. Hasil penelitian menemukan bahwa (1) hasil belajar IPS siswa dengan media pembelajaran word square termasuk dalam kategori tinggi, (2) hasil belajar Ekonomi siswa dengan pembelajaran konvensional termasuk dalam kategori sedang, (3) terdapat perbedaan yang signifikan pada hasil belajar Ekonomi siswa antara kelompok siswa dengan media word square dan kelompok siswa dengan pembelajaran konvensional). Dapat disimpulkan bahwa penggunaan media pembelajaran word square berpengaruh untuk meningkatkan hasil belajar Ekonomi siswa.Kata kunci: word square, konvensional, hasil belajar